(untitled) (Dharma: Bogor Journal of Community Service, 2026)
This Community Service Program (PkM) focuses on Training on Digitalization and Creative Content Development for PKK Women in Mbangmalang Cepit. The program was initiated in response to the low level of productive smartphone use, limited skills in digital content creation, and insufficient understanding of digital marketing strategies and monetization opportunities among PKK members. These conditions highlight the need to enhance digital literacy as a means of fostering home-based creative economic development. The program was designed to address these challenges through basic digital literacy training, workshops on creative content creation using simple applications, and the introduction of digital marketing strategies and content monetization techniques. The implementation employed the Participatory Action Research (PAR) method, targeting housewives with flexible time availability, a moderate education level, and high smartphone ownership that had not yet been optimally utilized. The results indicate a significant improvement in participants’ knowledge and skills in digital content production, as well as increased economic potential through the use of digital platforms. The program outputs include publications in community service journals, articles in electronic mass media, and enhanced economic capacity among the partners. Overall, this initiative supports the implementation of the national digital economy policy by promoting women’s empowerment and strengthening community-based creative economies through digital transformation.